The Identification of Misconceptions of Physics Education Students at Universitas Sriwijaya Using Four-Tier Diagnostic Test on Static Fluid Material - Sudirman Sudirman; Nur Julia Ningsih; Saparini Saparini; Melly Ariska; Nely Andriani; Abidin Pasaribu (Journal of Mathematics Science and Computer Education, 2023)
This study aims to identify students' misconceptions regarding static fluid material. It was conducted on 33 students enrolled in the fifth semester of the Physics Education Study Program at FKIP Universitas Sriwijaya during the academic year 2022/2023. Data was collected by giving a four-tier diagnostic test and conducting interviews. The Four-Tier Diagnostic Test consists of four-level multiple-choice questions with answers and reasons, as well as the level of confidence that can be used to identify misconceptions in students. The results of this study indicate that students who have misconceptions about static fluid materials fall into the moderate category, with the highest percentage compared to other conception categories. This demonstrates that misperceptions remain a problem that must be addressed promptly so prospective educators do not bring the incorrect concept. The sub-concepts that identified misconceptions from those with the highest percentage were: Hydrostatic Pressure, Pascal's Law, and Archimedes' Law.